Serum Catecholamines and Dysautonomia in Diabetic Gastroparesis and Liver Cirrhosis. (August 2015) - Aslam, Naeem; Kedar, Archana; Nagarajarao, Harsha S.; Reddy, Kartika; Rashed, Hani; Cutts, Teresa; Riely, Caroline; Abell, Thomas L.
Abstract: Background: Plasma catecholamine influences autonomic function and control, but there are few reports correlating them. In this study, 47 individuals (mean age, 38 years) were studied: 19 diabetes mellitus (DM) patients with gastroparesis, 16 with liver disease and 12 control subjects. Methods: Noninvasive autonomic function was assessed for sympathetic adrenergic functions as peripheral vasoconstriction in response to cold stress test and postural adjustment ratio (PAR) and cholinergic function as Valsalva ratio, represented by change in R-R intervals. Measurements were compared by analysis of variance and Spearman's correlation, and results were reported as mean ± standard error. Results: Plasma norepinephrine (1902.7 ± 263.3; P = 0.001) and epinephrine (224.5 ± 66.5; P = 0.008) levels, as well as plasma dopamine levels (861.3 ± 381.7), and total plasma catecholamine levels were highest for patients with liver disease, who also had significant negative correlation between norepinephrine level and vasoconstriction ( P = 0.01; r = −0.5), PAR1 ( P = 0.01; r = −0.5), sympathetic adrenergic functions ( P = 0.005; r = −0.6), total autonomic index ( P = 0.01–0.5) and total autonomic function ( P = 0.01; r = −0.2) and also negative correlation between epinephrine plasma level and total autonomic function ( P = 0.04; r = 0.4). DM patients were next highest in norepinephrine level (133.26 ± 7.43), but lowest for plasma catecholamine; a positive correlation between dopamine level and PAR1 ( P = 0.008; r = 0.6) was also seen in this group. Plasma dopamine levels and spider score correlated negatively ( P = 0.04; r = −0.5) and total plasma catecholamine positively with encephalopathy ( P = 0.04; r = 0.5) in patients with liver disease. Conclusions: Plasma catecholamine levels correlated with adrenergic functions in control subjects and patients with DM and liver disease, with no significant correlation seen for cholinergic function.